Genomic and mutational analysis of Pseudomonas syringae pv. tagetis EB037 pathogenicity on sunflower - Jude E. Maul; John Lydon; Dilip Lakshman; Colin Willard; Hyesuk Kong; Daniel P. Roberts (BMC Microbiology)
Abstract Background Pseudomonas syringae pv. tagetis (Pstag) causes apical chlorosis on sunflower and various other plants of the Asteraceae family. Whole genome sequencing of Pstag strain EB037 and transposon-mutant derivatives, no longer capable of causing apical chlorosis, was conducted to improve understanding of the molecular basis of disease caused by this pathogen. Results A tripartite pathogenicity island (TPI) for a Type III secretion system (T3SS) with the complete hrp-hrc gene cluster and conserved effector locus was detected in the Pstag genome. The exchange effector region of the TPI contained genes potentially functioning in detoxification of the environment as well as two integrases, but no previously described T3SS effector homologues. In all, the Pstag EB037 genome contained homologues for at least 44 T3SS effectors with 30 having known functions. Plasmids similar with pTagA and pTagB of P. syringae pv. tagetis ICMP 4091 were also identified in the Pstag genome. The pTagA-like plasmid contained a complete Type IV secretion system (T4SS) with associated putative killer protein. Mutational analysis using transposon insertions within genes functioning in the T3SS and T4SS confirmed the role of both secretion systems and these plasmids in apical chlorosis. Transposon mutagenesis identified an additional 22 genes in loci, including two more plasmid-bound loci, involved in apical chlorosis on sunflower; some with known importance in other plant or animal pathosystems. Conclusions Apical chlorosis disease caused by Pstag EB037 is the result of a complex set of mechanisms. This study identified a TPI and homologues for at least 44 T3SS effectors, 30 of which with known functions in disease, and another 20 genes in loci correlated with apical chlorosis on sunflower. Two plasmids were detected that were correlated with apical chlorosis disease, one of which contained a complete T4SS that was correlated with disease. To our knowledge, we provide the first direct evidence for a T4SS functioning in disease by a pathogenic P. syringae strain.